Is mom energy efficient? a study of gender, household energy consumption and family decision making in Indonesia - Permana, Ariva Sugandi (Elsevier, 2015)
This study highlights gender-related factors and attempts to understand their influence in residential energy consumption. This pilot study was done in Bandung City, Indonesia. It employed a questionnaire survey and face to face interviews. Questionnaires were randomly distributed to the households in Bandung City. In this study, energy consumption included household uses of power for lighting, entertainment, thermal comfort and cooking. Energy consumption was estimated based upon electrical and liquefied petroleum gas (LPG) consumption. The results showed that when the decisions about energy expenditure and control of energy consumption in the household were solely made by a woman, energy consumption tended to be the lowest. There are three possible ways decision can be made, by the wife, husband and a joint decision. This evidence suggests several things. They are that (1) women are good household energy managers, (2) men may be careless with respect to energy consumption, (3) women may be more cautious about household expenditures, and (4) when joint decisions were made the husband and wife relied-upon-each-other in reaching agreement. This suggests useful entry points for energy efficient initiatives